Carceral fantasies : cinema and prison in early twentieth-century America - Griffiths, Alison, 1963- (Film and culture., 2016)
A groundbreaking contribution to the study of non-theatrical film exhibition, Carceral Fantasies tells the little-known story of how cinema found a home in the U.S. penitentiary system and how the prison emerged as a setting and narrative trope in modern cinema. Focusing on films shown in prisons before 1935, the book explores the unique experience of viewing cinema while incarcerated and the complex cultural roots of cinematic renderings of prison life. Considering a diverse mix of cinematic genres, from early actualities and reenactments of notorious executions to reformist exposés of the 19.